Zwitterionic Polymers: Tuning of Smart Multifunctional Polymer Coatings Made by Zwitterionic Phosphorylcholines (Adv. Mater. Interfaces 1/2020). Issue 1 (10th January 2020) - Münch, Alexander S.; Adam, Stefan; Fritzsche, Tina; Uhlmann, Petra
Abstract : How is it possible to remove oily impurities from surfaces with pure water without the use of surfactants? In article number 1901422 by Alexander Münch, Petra Uhlmann, and co‐workers, a new functional coating is achieved by preparing thin films of ultra‐hydrophilic and swellable co‐polymers. Due to the formation a highly swollen polymer film in contact with water, the oil droplets cannot interact with the surface anymore and float away.